ANALISIS PENGARUH PRICE TO BOOK VALUE, INDEKS HARGA SAHAM GABUNGAN (IHSG) TERHADAP RETURN HARGA SAHAM SEBELUM DAN PADA SAAT PANDEMI PADA PERUSAHAAN TELEKOMUNIKASI - Ikrom, Ikrom; Suliswanto, Muhammad Sri Wahyudi; Fuddin, Muhammad Khoirul (Program Studi Ekonomi Pembangunan, 2022)
The purpose of this study is to determine and analyze the effect of price to book value, the composite stock price index, and the covid-19 dummy on the stock price of the telecommunications sector per quarter in 2019-2020. This study uses panel data and hypothesis testing. The results of this study indicate that price to book value, the composite stock price index, and the covid-19 dummy have a positive and significant effect on stock prices in the telecommunications sector. This proves that if the stock price increases by 1%, the price to book value, the joint stock price index, and the dummy will also increase.